THE EFFECT OF MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT SENTRAL CAWANG HOTEL EAST JAKARTA - Suprapto, Joko; Vijaya, Suryo Prawiro Utomo Murty (Yayasan Education and Social Center, 2026)
The purpose of this study was to determine the partial and simultaneous effects of motivation and work discipline on employee performance at Sentral Cawang Hotel, East Jakarta. This research used a quantitative method. The sampling technique used was saturated sampling, yielding 61 respondents. Data analysis techniques included validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results showed that motivation has a significant effect on employee performance with a coefficient of determination of 51.8%, and the hypothesis test indicated that t count > t table (4.587 > 2.001). Work discipline also has a significant effect on employee performance, with a coefficient of determination of 61.7%, and the hypothesis test showed t-count > t-table (8.639 > 2.001). Simultaneously, motivation and work discipline have a significant effect on employee performance, as indicated by the regression equation Y = 33.374 + 0.080X1 + 0.196X2. The coefficient of determination value is 82.7%, while the remaining 17.3% is influenced by other variables not examined in this study. Hypothesis testing resulted in an F-count value greater than the F table (84.318 > 3.156).